2013
DOI: 10.4161/cam.24804
|View full text |Cite
|
Sign up to set email alerts
|

Predicting how cells spread and migrate

Abstract: CoMMentAryCommentary to: Kim DH, Wirtz D. Focal adhesion size uniquely predicts cell migration. FASEB J 2013; 27:1351-61

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 38 publications
9
52
1
Order By: Relevance
“…Cell motility requires the transmission of force through focal adhesions, and focal adhesion size has been shown to correlate directly with cell velocity (44). Therefore, the effect of focal adhesions on cell velocity induced by hypoxia was investigated by generating MDA-MB-231 subclones stably transfected with shEV vector or a vector encoding either of two independent shRNAs targeting FAK (Fig.…”
Section: Focal Adhesions Are Required For Enhanced Cell Motility Undermentioning
confidence: 99%
“…Cell motility requires the transmission of force through focal adhesions, and focal adhesion size has been shown to correlate directly with cell velocity (44). Therefore, the effect of focal adhesions on cell velocity induced by hypoxia was investigated by generating MDA-MB-231 subclones stably transfected with shEV vector or a vector encoding either of two independent shRNAs targeting FAK (Fig.…”
Section: Focal Adhesions Are Required For Enhanced Cell Motility Undermentioning
confidence: 99%
“…Although cytoskeleton is important for cell shape and their spreading on ECM matrix (57), the extent and size of the focal adhesion complex will dictate the robustness in adhesion of cells on the surfaces (58). Our data showed that although no drastic differences were observed in the pattern of stress fibers visualized by F-actin staining, a difference in FAK staining was observed in cells attached on collagen and amyloid surfaces (Fig.…”
Section: Resultsmentioning
confidence: 41%
“…Immunofluorescence measurements of vinculin, a component of the FA complex, revealed a significant increase in the average area of FAs in FL2-depleted U2OS cells compared to controls (0.87±0.07 m 2 in controls vs. 2.54±0.18 m 2 in FL2 siRNA-treated cells; Figure 3 c and d). Though FA area has long been thought to negatively correlate with migration speed (Gardel et al 2011), recent reports have identified a biphasic relationship in which cells move faster with increased FA area up to a threshold point, beyond which cell migration slows down (Kim and Wirtz 2013a, 2013b). Strikingly, the average area of FAs in FL2 depleted cells, 2.54µm 2 , is almost identical to the FA area shown by Kim and Wirtz to correlate with the fastest migration speed in fibroblasts (Kim and Wirtz 2013a).…”
Section: Resultsmentioning
confidence: 99%